2020
DOI: 10.1111/joca.12311
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants, Financial Knowledge, and Financial Behavior

Abstract: This research seeks to identify gaps in financial knowledge and behaviors between immigrants to Canada and individuals who are born in Canada. The research aims to evaluate to what extent immigrants involve themselves in financial planning and avoid harmful financial behaviors. Employing the Canadian Financial Capability Survey (2009), the findings of the study suggest that immigrants are less likely to show high levels of financial knowledge compared to born citizens. The knowledge gap between immigrants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…O'Connor (2019) extended the connection from financial capability to racial and ethnic identity, when they noted that “minorities typically exhibit lower levels of financial knowledge than other population segments” (p. 391). Rostamkalaei and Riding (2020) found that newcomers to Canada, often having lower‐than‐average incomes, have lower levels of financial capability as compared with other Canadian residents, but that the gap diminishes over time. This noteworthy study raises two important issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…O'Connor (2019) extended the connection from financial capability to racial and ethnic identity, when they noted that “minorities typically exhibit lower levels of financial knowledge than other population segments” (p. 391). Rostamkalaei and Riding (2020) found that newcomers to Canada, often having lower‐than‐average incomes, have lower levels of financial capability as compared with other Canadian residents, but that the gap diminishes over time. This noteworthy study raises two important issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third and relatedly, structural inequalities and immigrants' lack of certainty about the future can lead to a disadvantage in annuity income. Immigrants have systematically less knowledge about the U.S. retirement system and lower financial literacy than the native-born (Rostamkalaei and Riding 2020), which makes personal financing a challenging task. Many experience uncertainty about whether they will stay in the U.S. for the long term, especially when host country immigration policies are changeable and difficult to navigate (Ayón and Becerra 2013;Rincón 2017).…”
Section: Latent Cumulative (Dis)advantage and Older Immigrants' Incomementioning
confidence: 99%
“…Having sufficient financial literacy and sound financial attitudes are prerequisites for migrant workers to achieve their goals through sound financial behavior (Rostamkalaei and Riding, 2020; World Bank, 2015). Studies have shown that identifying the purpose of a remittance as a target for financial action can lead to positive behavioral changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Limited access to formal financial services could decrease financial self-efficacy (Rostamkalaei and Riding, 2020) and hinder optimal financial behavior (Birkenmaier and Fu, 2019). Multiple factors could discourage migrant workers from accessing formal financial services (Atkinson and Messy, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation